On the Coherence in the Boundary Layer: Development of a Canopy Interface Model - Mauree, Dasaraden; Blond, Nadege; Kohler, Manon; Clappier, Alain (Frontiers in Earth Science, 2017)
A 1D Canopy Interface Model (CIM) is developed to act as an interface between a meso-scale and a micro-scale atmospheric model and to better resolve the surface turbulent fluxes in the urban canopy layer. A new discretisation is proposed to solve the TKE equation finding solutions that remain fully concordant with the surface layer theories developed for neutral flows over flat surfaces. A correction is added in the buoyancy term of the TKE equation to improve consistency with the Monin-Obukhov surface layer theory. Obstacles of varying heights and dimensions are taken into account by introducing specific terms in the equations and by modifying the mixing length formulation in the canopy layer. The results produced by CIM are then compared with wind and TKE profiles simulated with a LES experiment and results obtained during the BUBBLE meteorological intensive observation campaign. It is shown that the CIM computations are in good agreement with the results simulated by the LES as well as the measurements from BUBBLE. The applicability of the correction term in an urban canopy layer and to further validate CIM in multiple stability conditions and various urban configurations is discussed.